Geoprocessing applied to the assessment of environmental noise: a case study in the city of Sorocaba, São Paulo, Brazil - Costa, Samuel Barsanelli [UNESP]; Lourenço, Roberto Wagner [UNESP] (Springer, 2011)
Noise mapping has been used as an instrument for assessment of environmental noise, helping to support decision making on urban planning. In Brazil, urban noise is not yet recognized as a major environmental problem by the government. Besides, cities that have databases to drive acoustic simulations, making use of advanced noise mapping systems, are rare. This study sought an alternative method of noise mapping through the use of geoprocessing, which is feasible for the Brazilian reality and for other developing countries. The area chosen for the study was the central zone of the city of Sorocaba, located in So Paulo State, Brazil. The proposed method was effective in the spatial evaluation of equivalent sound pressure level. The results showed an urban area with high noise levels that exceed the legal standard, posing a threat to the welfare of the population.
Keywords: Environmental noise; Noise mapping; Geoprocessing; Urban planning